Análisis de la validez de la aplicación de las guías de ASGE en pacientes con coledocolitiasis. - Bravo García, Dahira Abigail (2024)
Choledocholithiasis, which is the presence of gallstones in the common bile duct, is the main cause of bile duct obstruction, leading the patient to severe complications and even triggering post-ERCP cholangitis and pancreatitis. This is why ASGE (American Society for Gastrointestinal Endoscopy/American Society for Gastrointestinal Endoscopy) has established some clinical, laboratory and imaging criteria that confirm the suspicion of Choledocholithiasis, in order to adapt the most optimal treatment and conduct to be taken and thus avoid less hospitalization time, reduce costs and avoid complications after malpractice when deciding the need for laparoscopic cholecystectomy, endoscopic ultrasound, ERCP or MRCP that the patient requires. These criteria have a diagnostic accuracy of more than 70% of effectiveness and are classified as very strong, strong and moderate, constituting one of the most accepted and globally recognized predictive scales proposed by the above-mentioned society, same one that is responsible for stratifying or classifying patients according to their risk of being diagnosed with Choledocholithiasis. Thus, the objective of the study was to rescue the validity of the ASGE Clinical Guidelines in the diagnosis of Choledocholithiasis to avoid future complications caused by inadequate medical conduct and condition management, through the use of bibliographic sources, Society Guides and observational studies, experimental, cross-sectional and retrospective studies with analytical interest that validate the usefulness of the criteria and the advantages and disadvantages of putting them into practice during professional practice, thanks to the implementation of these guidelines it has been possible to stop the development of Post-ERCP Pancreatitis, which is one of the most prevalent complications after performing Endoscopic Retrograde Cholangiopancreatography without criteria, since currently, these clearly identified diseases of biliary origin help the doctor to have an appropriate diagnostic approach.